How to effectively use interactivity to improve visual analysis in groups of novices or experts - Viana, Maria do Mar (2022)
Viana, M. D. M., & Cabral, P. (2020). How to effectively use interactivity to improve visual analysis in groups of novices or experts. In CAPSI 2020. 20ª Conferência da Associação Portuguesa de Sistemas de Informação, "Artificialização, Humanização: Os desafios dos Sistemas de Informação na transformação da sociedade". [20th Portuguese Association of Information Systems Conference] (pp. 1-18). [33] Associação Portuguesa de Sistemas de Informação. Link: https://aisel.aisnet.org/capsi2020/33